A Balamuthia survivor. Issue 3 (28th June 2016) - Vollmer, Michael Eric; Glaser, Carol
Abstract : Introduction: This case report describes a human survivor of Balamuthia mandrillaris infection. This is a free-living amoeba that can cause infection with the devastating consequence of near universally fatal encephalitis. We report this case to demonstrate the possibility of recovery. Case presentation: A 26-year-old Hispanic male, a landscape gardener, presented to the hospital in March 2010 with a two month history of headache, visual disturbances and new-onset seizures. Brain imaging identified two enhancing central lesions and Balamuthia mandrillaris was later identified by brain biopsy. He received several months of various antimicrobials including miltefosine, a novel use of the drug in this disease at the time. Seven weeks into therapy, considerations were made to switch him to 'comfort care' because of worsening clinical status and seemingly lack of response to treatment. The patient finally demonstrated clinical and radiological improvement after eight weeks with modified therapy, despite experiencing some debilitating toxic effects likely to be related to antibiotics. Two years after his initial presentation he made a complete recovery. Conclusion: Balamuthia mandrillaris amoebic encephalitis is considered an almost universally fatal disease; this case demonstrates the possibility of recovery. This report outlines his treatment, drug toxicities and includes additional information regarding the therapeutic use of the drug miltefosine. Whether his survival is related to the specific antimicrobials used in this case is unknown and further investigation is warranted.